Opportunities and Challenges of Islamic Banks during the Covid-19 Pandemic - Zulfikar Hasan; Nurul Syahira (Jurnal Multidisiplin West Science, 2022)
The COVID-19 pandemic in Indonesia has significantly impacted the economy, including the banking sector. But not with Islamic banking, which instead shows a positive trend. Even though sharia banking is showing a positive direction, the penetration rate of the sharia banking market in Indonesia is still relatively low compared to conventional banking. This research was structured to interpret the opportunities and challenges faced by Islamic banks during the Covid-19 pandemic. This study uses qualitative data analysis with a descriptive-critical method and through a literature study approach. This data analysis only focuses on the opportunities and challenges of Islamic banks during the pandemic. Researchers use secondary data to obtain discussion of this research that comes from books, the internet and research journals that have the same topics as those that researchers discuss. Based on the results of this research, there are opportunities and challenges for Islamic banks during the Covid-19 pandemic. Opportunities for Islamic banks during the pandemic are related to increasing assets, expanding market penetration, and efficiency in operational costs. Meanwhile, financing and operational risks are major challenges that need attention.